The binding mechanism of adhesin P subtype to globotetraosylceramide is associated with systemic disease - Johansson MM; Bélurier E; Papageorgiou AC; Sundin AP; Rahkila J; Kallonen T; Nilsson UJ; Maatsola S; Nyholm TKM; Käpylä J; Corander J; Leino R; et al. (American Society for Biochemistry and Molecular Biology, Inc., 2022)
Streptococcus suis is part of the pig commensal microbiome but strains can also be pathogenic, causing pneumonia and meningitis in pigs as well as zoonotic meningitis. According to genomic analysis, S. suis is divided into asymptomatic carriage, respiratory and systemic strains with distinct genomic signatures. Since the strategies to target pathogenic S. suis are limited, new therapeutic approaches are needed. The virulence factor S. suis adhesin P (SadP) recognizes the galabiose Galα1-4Gal-oligosaccharide. Based on its oligosaccharide fine specificity, SadP can be divided into subtypes PN and PO We show here that subtype PN is distributed in the systemic strains causing meningitis, whereas type PO is found in asymptomatic carriage and respiratory strains. Both types of SadP are shown to predominantly bind to pig lung globotriaosylceramide (Gb3). However, SadP adhesin from systemic subtype PN strains also binds to globotetraosylceramide (Gb4). Mutagenesis studies of the galabiose-binding domain of type PN SadP adhesin showed that the amino acid asparagine-285, which is replaced by an aspartate residue in type PO SadP, was required for binding to Gb4 and, strikingly, was also required for interaction with the glycomimetic inhibitor phenylurea-galabiose. Molecular dynamics simulations provided insight into the role of Asn-285 for Gb4 and phenylurea-galabiose binding, suggesting additional hydrogen bonding to terminal GalNAc of Gb4 and urea-group. Thus, the Asn-285-mediated molecular mechanism of type PN SadP binding to Gb4 could be used to selectively target S. suis in systemic disease without interfering with commensal strains, opening up new avenues for interventional strategies against this pathogen.